EFFECT OF MAIZE SEEDS SOAKING WITH ACIDS OF ASCORBIC, CITRIC AND HUMIC ON FIELD EMERGENCE - & Hamza, Kadhim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
A field experiment was conducted during two spring seasons in 2019 and 2020 to achieve rapid, uniform, and high ratio of field emergence of maize seeds (cv. Baghdad3). Randomize complete block design was used with three replications. Seeds were soaked in acids of ascorbic and citric (100 mg l-1) and humic (1 ml l-1) for 18 hours, as well as control treatment (seeds soaking in distilled water only). The results showed the significant superiority of soaking treatment in humic acid, which gave averages of field emergence properties in both seasons as follows: last day of field emergence (12.6 and 12.9 days), difference between first and last day of field emergence (4.8 and 4.9 days), ratio of field emergence at first count (49.5 and 55.5%), ratio of field emergence at final count (93.2 and 93.2%), daily average of field emergence (7.8 and 7.8 days), average of field emergence time (9.0 and 8.8 days) and index of field emergence average (10.5 and 10.7 days). It can be concluded that seeds soaking in humic acid improved properties of emergence and seedlings; therefore it can be recommended to soak maize seeds in humic acid (1 ml l-1) for 18 hours when planting in the spring season.